Synthesis, Characterization and Application of Carbon Nanotubes and Carbon Nanofibers - Hussien, Muataz Ali Atieh (2005)
Well aligned multi wall carbon nanotubes (MWCNTs), carbon nanofibers (CNFs) and other type of carbon nanostructure materials have been synthesized by a fabricated floating catalyst chemical vapor deposition (FC-CVD) method. This involved the pyrolysis of benzene-ferrocene vapor mixture. The CVD parameters (Hydrogen flow rate, reaction time and reaction temperature) were studied to selectively synthesize nanotubes and nanofibers with required dimensions. Carbon nanotubes films with a diameter of 2-50 nm and nanofiber with a diameter range from 100-300 nm were synthesized in a benzenelhydrogen atmosphere. Furthermore vapor grown carbon fibers have been synthesized with different diameters and lengths. Iron clusters that were produced from the thermal decomposition of ferrocene films were used as catalyst for the synthesis of the carbon structures.The effects of different hydrogen flow rates (50-500 ml/min) on the morphology, quality and quantity of the product were investigated. Maximum yield and purity was obtained at 300 ml/min. The effect of the reaction time on the purity and yield of carbon nanotubes was studied from 1 minute to 60 minutes. There was no effect of the reaction time on the average diameter while maximum yield of carbon nanotubes was achieved at 45 minutes. The last variable was the reaction temperature, which was varied from 500 "C to 1200 "C. By controlling the growth temperature, carbon nanotubes (CNTs), carbon nanofibers (CNFs) and vapor grown carbon fiber with different structures were produced. Increasing the temperature has a remarkable effect on the size and shape of the catalyst and this in turn affected the diameter distribution and structure of the carbon materials. The carbon nanotubes were produced from 600 "C to 850 "C with maximum yield at 850 "C, while for the production of carbon nanofibers the reaction temperature was from 900 "C to 1000 "C with a maximum yield at 1000 "C. Vapor grown carbon fibers were produced at 1050 "C to 1200 "C with maximum yield at 1050 "C. The synthesised nanotubes/nanofibers were investigated by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) .The thermal degradation kinetics of CNTs was investigated by dynamic thermogravimetry, in an air atmosphere, over the temperature range 25 - 800 "C and at constant nominal heating rate 10 "C / min. The corresponding activation energies, frequency factors and reaction orders were determined. Homogenous distribution of MWCNTsICNFs in natural rubber (NR) was achieved by ultrasonic assisted solution-evaporating method. Addition of 1-10 wt% of CNFs and CNTs to natural rubber as nanocomposite increased the rubber mechanical properties significantly. The properties of the composites such as tensile strength, tensile modulus, and elongation at break were studied. In addition to mechanical testing, the dispersion state of the MWNTs into NR was studied by TEM in order to understand the morphology of the resulting system. The result indicated that, by increasing the amount of CNTs and CNFs into the natural rubber the ductility decreased and the material became stronger and tougher but at the same time more brittle. The results showed that by adding 1 wt% of CNTs and CNFs to NR the stress level were increased sharply to 0.56413 and 0.54 MPa respectively compared to NR which was 0.2839 MPa. At 10 wt% the stress level of CNTs with NR were increased sharply 9 times and reached to 2.55 MPa while for CNFs it increased 4.66 times and reached to 1.33 MPa.